Analytical Ultracentrifugation 2016
DOI: 10.1007/978-4-431-55985-6_21
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutical Evaluation of Intermolecular Interactions by AUC-SE

Abstract: Analytical ultracentrifugation sedimentation equilibrium (AUC-SE) is a useful technique to investigate the weak reversible intermolecular interactions among proteins in solution. It provides biophysical information such as the average apparent molecular weight, stoichiometry, and association constant of associating proteins. Several studies of intermolecular interaction in biopharmaceuticals by AUC-SE are introduced in this chapter. AUC-SE also provides the second virial coefficient (B 2 ), which represents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A k D value of −20 mL/g was a threshold for LLPS where the B 2 value indicated zero in this case study. Previous studies [ 28 30 , 35 38 ] have also demonstrated a linear relationship between the k D and B 2 values. The investigations by Connolly et al [ 28 ] indicated this relationship among eight different mAbs and corroborated our results.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…A k D value of −20 mL/g was a threshold for LLPS where the B 2 value indicated zero in this case study. Previous studies [ 28 30 , 35 38 ] have also demonstrated a linear relationship between the k D and B 2 values. The investigations by Connolly et al [ 28 ] indicated this relationship among eight different mAbs and corroborated our results.…”
Section: Discussionmentioning
confidence: 56%
“…The B 2 was −4.08 × 10 −5 mL·mol/g 2 and the k D was −33 mL/g for the WT. The sign for B 2 suggests the existence of attractive protein–protein intermolecular interactions [ 11 , 20 , 21 , 26 , 29 , 30 ]. The addition of 150 mM NaCl increased the k D value from −33 mL/g to −12 mL/g, indicating that the protein–protein self–attractive interactions in low–ionic–strength buffer A could essentially be mediated by electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Composition gradient static light scattering (CG-SLS) is another approach to investigate self-and hetero-associations of proteins at high concentration (Attri and Minton 2005). By using CG-SLS, the second virial coefficient of the IgG-IgG interaction was determined over the range of concentrations up to >150 mg/mL (Kress et al 2016), allowing assessment of the extent of intermolecular interactions and thus being a useful tool for the rational formulation development (Saito and Uchiyama 2016).…”
Section: Challenges Of Auc Application For Characterization Of Highlymentioning
confidence: 99%